Chemical Stability of Mesoporous Oxide Thin Film Electrodes under Electrochemical Cycling: from Dissolution to Stabilization - Alberti, Sebastián (2019)
Mesoporous oxide thin films (MOTF) present very high surface areas and highly controlled monodisperse pores in the nanometer range. These features spurred their possible applications in separation membranes and permselective electrodes. However, their performance in real applications is limited by their reactivity. Here, we perform a basic study of the stability of MOTF toward dissolution in aqueous media using a variety of characterization techniques. In particular, we focus in their stability behavior under the influence of ionic strength, adsorption of electrochemical probes, and applied electrode potential. Mesoporous silica thin films present a limited chemical stability after electrochemical cycling, particularly under high ionic strength, due to their high specific surface area and the interactions between the electrochemical probes and the surface. In contrast, TiO2 or Si0.9Zr0.1O2 matrices present higher stability; thus, they are an adequate alternative to produce accessible, sensitive, and robust permselective electrodes or membranes that perform under a wide variety of conditions.